Efektivitas Pembelajaran Kooperatif Team Games Tournament melalui Media Puzzle terhadap Keterampilan Kolaborasi Siswa dalam Pembelajaran Bahasa Indonesia SDN 01 Ngadirenggo - Sari, Adel Lia Novita; Yulia, Lina; Abadi, Machrus (Medan Resource Center, 2023)
Collaboration skills are important to be optimized through learning activities in the current era. This study aims to determine the effectiveness of Team Games Tournament cooperative learning through puzzle media on student collaboration skills in Indonesian learning at SDN 01 Ngadirenggo. This research is qualitative descriptive research. The subjects in this study were students of SDN 01 Ngadirenggo. Data collection techniques are carried out by observation of students, interviews with teachers and documentation. Data analysis is carried out in three stages including data reduction, data presentation, and conclusions. The results of this study describe the form and effectiveness of Team Games Tournament cooperative learning through puzzle media on student collaboration skills in Indonesian learning at SDN 01. Based on existing data, the application of cooperative learning assisted by puzzle media is effective in improving the collaboration ability of SDN 01 Ngadirenggo students.